Clinical features, visual outcome and association with systemic disease in patients with episleritis and scleritis. A study of 50 eyes - Mohamed Anjum Iqbal; Radha Annamalai; Muthayya Muthukumar (International Journal of Medical Research and Review, 2016)
Introduction: Episcleritis and scleritis are inflammatory disorders which can have an acute presentation and are frequently encountered by primary care practitioners.Episcleritis is a benign, self-limited disease that resolves within 2 to 3 weeks. Scleritis is painful, causing visual loss due to uveitis, glaucoma, cataract, and retinal detachment. Both are associated with underlying systemic diseases.We aim to report clinical features, visual outcome and association with systemic disease in patients with visual symptoms.Methods: This is a prospective cohort study conducted on 50 patients over 1 year in a tertiary eye care hospital Complete ophthalmic evaluation was performed. Patients were followed up for one year to look for response to treatment and development of complications.Results: In our study, the incidence of episcleritis was more frequent than scleritis. The age group affected was 34 to 52 years and more in women. Most of our patients with episcleritis showed resolution within 3 weeks. Scleritis was associated with decreased vision and more complications. In both forms of inflammation rheumatoid arthritis, systemic lupus erythematosus and psoriasis were the most common etiology.Conclusion: In rheumatoid arthritis, systemic lupus erythematosus and psoriasis patients, episcleritis and scleritis can be the initial clinical presentation. Clinical features are more severe in scleritis and can be diagnosedwith B scan ultrasound. Visual loss in both can be prevented by early treatment. We found the association with rheumatoid arthritis and SLEto be high in our population. Infections were not as common as autoimmune diseases in the population studied.